2017
DOI: 10.1590/1980-5373-mr-2016-0615
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Performance of Titanates with Formula MTiO3 (M= Fe, Ni, and Co) Synthesized by Solvo-Combustion Method

Abstract: This work reports the synthesis of a variety of materials with an ilmenite-type structure MTiO 3 formula, where M= Fe, Co, and Ni, these materials were synthesized by the method of solvo-combustion, a simple and rapid method. These materials were characterized by X-ray Diffraction (XRD), scanning electron microscopy (SEM), FT-IR spectroscopy, thermogravimetric analysis (TGA/DTA), surface area determination by the BET method and analysis of particle size. The photocatalytic activity was measured in the degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 33 publications
1
3
0
1
Order By: Relevance
“…The UV–vis absorption spectra of our systems show a band shift from 554 nm, the maximum absorption of RhB, to 530 nm (Figure S23). As reported earlier, this effect indicates that photodegradation occurs via N-deethylation. It was found that the photodegradation of RhB was negligible if the experiment was performed under an argon atmosphere, indicating that the presence of oxygen is essential. Generally, it is known that when a photocatalyst is irradiated by light, various generated reactive oxygen species (ROS) can degrade the pollutants.…”
Section: Resultssupporting
confidence: 55%
“…The UV–vis absorption spectra of our systems show a band shift from 554 nm, the maximum absorption of RhB, to 530 nm (Figure S23). As reported earlier, this effect indicates that photodegradation occurs via N-deethylation. It was found that the photodegradation of RhB was negligible if the experiment was performed under an argon atmosphere, indicating that the presence of oxygen is essential. Generally, it is known that when a photocatalyst is irradiated by light, various generated reactive oxygen species (ROS) can degrade the pollutants.…”
Section: Resultssupporting
confidence: 55%
“…Perovskite oxide has been proven to be an important class of photocatalysts 7 . As one of the perovskite photocatalysts, BiFeO 3 exhibits visible-light-driven photocatalytic activity for the degradation of dyes and water splitting due to its narrow bandgap and chemical stability [8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…with other cations, including alkaline ions (Li + , Na + , K + , Rb + , Cs + ) [20], transition (Co 2+ , Ni 2+ , Fe 3+ , Cu 2+ , Zn 2+ , Cd 2+ ) [20,26,27] and noble metals (Au, Pt, Pd, Ru, Ag) [28,29]. Along with the iron titanate nanotubes, the literature is moderately limited [9,21,26,27,[30][31][32][33][34][35][36][37][38]. Attention has been focused on the electrochemistry [32,38], photocatalysis [31,33,36,37], molecular segregation [27], optical and magnetic properties [21,26,27,31,33] of Fe-titanates.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the iron titanate nanotubes, the literature is moderately limited [9,21,26,27,[30][31][32][33][34][35][36][37][38]. Attention has been focused on the electrochemistry [32,38], photocatalysis [31,33,36,37], molecular segregation [27], optical and magnetic properties [21,26,27,31,33] of Fe-titanates. Notwithstanding research and development efforts into the properties of Fe-titanate nanotubes, including the intrinsic ability of iron when present in titanate nanotubes in building carbon domains via catalytic decomposition from light carbon feedstocks, have not been widely explored so far.…”
Section: Introductionmentioning
confidence: 99%